The Fran with four brains - Benton, Jim (New York : Simon & Schuster Books for Young Readers, 2006)
With so much on her plate, like creating monsters out of meat by-products and dealing with overgrown babies, mad scientist Fran decides that the only way to get all her tasks done is to create Franbots, steel-plated duplicates of herself with minds of their own!
Ages 7-10.
Keywords: Science -- Experiments -- Juvenile fiction; Science -- Experiments -- Fiction; Robots -- Fiction; Schools -- Fiction; Humorous fiction